Entanglement and topological interfaces. Issue 6 (13th April 2016) - Brehm, E.; Brunner, I.; Jaud, D.; Schmidt‐Colinet, C.
Abstract : The entanglement entropies in twodimensional conformal field theories in the presence of topological interfaces is considered. Tracing over one side of the interface, the leading term of the entropy remains unchanged. The interface however adds a subleading contribution, which can be interpreted as a relative (Kullback‐Leibler) entropy with respect to the situation with no defect inserted. Reinterpreting boundaries as topological interfaces of a chiral half of the full theory, the authors rederive the left/right entanglement entropy in analogy with the interface case. We discuss WZW models and toroidalbosonic theories as examples. Abstract : In this paper we consider entanglement entropies in two‐dimensional conformal field theories in the presence of topological interfaces. Tracing over one side of the interface, the leading term of the entropy remains unchanged. The interface however adds a subleading contribution, which can be interpreted as a relative (Kullback‐Leibler) entropy with respect to the situation with no defect inserted. Reinterpreting boundaries as topological interfaces of a chiral half of the full theory, we rederive the left/right entanglement entropy in analogy with the interface case. We discuss WZW models and toroidal bosonic theories as examples.